Productivity and Nutritive Quality of Johnsongrass (Sorghum halepense) as Influenced by Commercial Fertilizer, Broiler Litter, and Interseeded White Clover (Trifolium repens). (4th January 2012) - Dillard, Sandra L.; Sturgeon, Laura E.; Owsley, Walter F.; Wood, C. Wesley; Holliman, James L.; Muntifering, Russell B.
Abstract : In the southeastern USA, there is an abundance of broiler litter from commercial poultry production that is available for use as fertilizer, but cropland and pastureland amended with broiler litter often exhibit greatly increased soil-test P. We evaluated productivity and nutritive quality of Johnsongrass ( Sorghum halepense ) that was interseeded with or without white clover ( Trifolium repens ) and which commercial fertilizer (ammonium nitrate and diammonium phosphate) or broiler litter was applied on the basis of soil-test P; broiler litter was supplemented with ammonium nitrate to be isonitrogenous with commercial fertilizer. Forage dry matter yield and foliar concentrations of crude protein, cell wall constituents, P, K, and Cu were not different among fertilizer treatments, and concentration of Zn was only slightly greater for forage amended with broiler litter than commercial fertilizer. Results indicate that broiler litter can be a cost-effective alternative to commercial fertilizer for warm-season forage production when applied on the basis of soil-test P.